Physician-pharmacist agreement about off-label use of medications in private clinical settings in Baghdad, Iraq - Hussain SA; Abbas AN; Alhadad HA; Al-Jumaili AA; Abdulrahman ZS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Objective: 1) To evaluate the relationship between physician-pharmacist agreement about the off-label drug use and 2) and to identify the most common off-label medication category/indications and prescriber clinical disciplines in private settings in Baghdad area, Iraq Methods: This study evaluated 980 off-label use requests in the private clinical settings within Baghdad area, Iraq from October 2013 to September 2015. The efficacy, safety, and convenience of each drug request and its alternative options were evaluated according to the patient health and demographic characteristics and standard guidelines. Results: Of the 980 physician off-label requests, only 22.7% were approved by the pharmacists. Rheumatology and Nephrology accounted for the highest ratio of off-label use requests for adults (30.3% and 26.3%). The pharmacist rejection ratio of off-label use was comparable between the two groups (p>0.05). Most of the issued requests were attributed either to unapproved indication or to combination of more than one drug (38% and 35.3%). A low acceptance rate was reported in the requests issued for treatment in different clinical lines to the authorized one (11.9%). The lowest rate of acceptance was reported in the requests that had very low evidence level (9.1%). The mostly prescribed medications were musculoskeletal agents (28.9%). Finally, 78.2% of the requests came from clinical branches for adults. Although the agreement rate for requests in adults was higher than that in pediatrics, the two rates were not significantly different. Conclusion: Community pharmacists should effectively take responsibility for assessing off-label drug requests in Iraqi private settings. The quality of evidence does not represent the major factor influencing the approval rate of off-label drug use. The availability of safer and/or affordable alternatives and prescribing for a different patient age category highly impacted the pharmacists' approval rate.